Allicin shows antifungal efficacy against Cryptococcus neoformans by blocking the fungal cell membrane - Li, Zhun; Li, Zhengtu; Yang, Jun; Lu, Chun; Li, Yongming; Luo, Yinzhu; Cong, Feng; Shi, Rongmei; Wang, Zhen; Chen, Huaying; Li, Xinxia; Yang, Jinglu; et al. (Frontiers in Microbiology, 2022)
Allicin, which is generated by the catalytic reaction between alliin and alliinase extracted from garlic, has been shown to have a wide range of antimicrobial activities, but its anti-Cryptococcus efficacy and mechanism are not quite clear. Here, we have determined that the Conversion rate of allicin in the reaction product reached 97.5%. The minimal inhibitory concentration (MIC) of allicin against Cryptococcus neoformans (C. neoformans) H99 was 2 μg/ml, which is comparable to fluconazole (FLU, 1 μg/ml). Furthermore, allicin exhibited effective antifungal activity against 46 clinical isolates of C. neoformans, and the MICs ranged from 1 to 8 μg/ml, even for AmB-insensitive strains. Interestingly, allicin also exerted additive or synergistic effects when combined with amphotericin B (AmB) and FLU. Time-killing curves and long-term live cell imaging of H99 showed that 4 MIC of allicin had fungicide activity. Additionally, allicin (4 and 8 mg/kg) exerted a dose-dependent therapeutic effect on H99-infected mice by significantly reducing the wet pulmonary coefficient and Cryptococcus load and reducing lung damage. Even the efficacy of 8 mg/kg was comparable to FLU (20 mg/kg). Transcriptomics revealed that allicin may act on the cell membrane of H99. Subsequently, transmission electron microscopy (TEM) observations showed that allicin clearly breached the cell membrane and organelles of H99. Confocal laser scanning microscopy (CLSM) results further confirmed that allicin disrupted the permeability of the cell membranes of H99 in a dose-dependent manner. Allicin exhibits strong anti-C. neoformans activity in vitro and in vivo, mainly by destroying the permeability and related functions of Cryptococcus cell membranes.